A hybrid neighbor optimization algorithm for SON based on network topology, Handover counters and RF measurements - Duarte, D. (2019)
With the increasing complexity of current wireless networks, it became evident the need for Self-Organizing Networks (SON), which aims to automate most of the associated radio planning and optimization tasks. Within SON, this paper aims to optimize the Neighbor Cell List (NCL) for radio network cells. An algorithm composed by three decision criteria was developed: geographic localization and orientation, according network topology, Radio Frequency (RF) measurements collected by drive-tests or traces and Performance Management (PM) counters from Handover (HO) statistics. The first decision, proposes a new NCL taking into account the Base Station (BS) location and interference tiers, based on the quadrant method. The last two decision criteria consider signal strength and interference level measurements and HO statistics in a time period, respectively. They also define a priority to each cell and added, kept or removed neighbor relation, based on user defined constraints. The algorithms were developed and implemented over new radio network optimization professional tool. Several case studies were produced using real data from a mobile operator.